Improving the quality of care with a single-entry model of referral for total joint replacement: a preimplementation/postimplementation evaluation. Issue 12 (23rd December 2019) - Damani, Zaheed; Bohm, Eric; Quan, Hude; Noseworthy, Thomas; MacKean, Gail; Loucks, Lynda; Marshall, Deborah A
Abstract : Objectives: We assessed: (1) waiting time variation among surgeons; (2) proportion of patients receiving surgery within benchmark and (3) influence of the Winnipeg Central Intake Service (WCIS) across five dimensions of quality: accessibility, acceptability, appropriateness, effectiveness, safety. Design: Preimplementation/postimplementation cross-sectional design comparing historical (n=2282) and prospective (n=2397) cohorts. Setting: Regional, provincial health authority. Participants: Patients awaiting total joint replacement of the hip or knee. Interventions: The WCIS is a single-entry model (SEM) to improve access to total hip replacement (THR) or total knee replacement (TKR) surgery, implemented to minimise variation in total waiting time (TW) across orthopaedic surgeons and increase the proportion of surgeries within 26 weeks (benchmark). Impact of SEMs on quality of care is poorly understood. Primary and secondary outcome measures: Primary outcomes related to 'accessibility': waiting time variation across surgeons, waiting times (Waiting Time 2 (WT2)=decision to treat until surgery and TW=total waiting time) and surgeries within benchmark. Analysis included descriptive statistics, group comparisons and clustered regression. Results: Variability in TW among surgeons was reduced by 3.7 (hip) and 4.3 (knee) weeks. Mean waiting was reduced for TKR (WT2/TW); TKR within benchmark increased by 5.9%. Accessibility and safety were the only quality dimensions that changed (post-WCIS THR and TKR). Shorter WT2 was associated with post-WCIS (knee), worse Oxford score (hip and knee) and having medical comorbidities (hip). Meeting benchmark was associated with post-WCIS (knee), lower Body Mass Index (BMI) (hip) and worse Oxford score (hip and knee). Conclusions: The WCIS reduced variability across surgeon waiting times, with modest reductions in overall waits for surgery. There was improvement in some, but not all, dimensions of quality.